Effectiveness of prophylactic intravitreal bevacizumab injection to proliferative diabetic retinopathy patients with elevated preoperative intraocular VEGF in preventing complications after vitrectomy - Tsubota K (Dove Medical Press, 2019)
Kinya Tsubota, Yoshihiko Usui, Yoshihiro Wakabayashi, Jun Suzuki, Shunichiro Ueda, Hiroshi GotoDepartment of Ophthalmology, Tokyo Medical University Hospital, Tokyo, JapanPurpose: This study aimed to elucidate the effects of intravitreal bevacizumab (IVB) injections for the prevention of post-vitrectomy complications in proliferative diabetic retinopathy (PDR) patients with elevated vitreous vascular endothelial growth factor (VEGF) concentration. Design: Prospective case series. Methods: Thirty-three patients (42 eyes) with PDR who underwent primary vitrectomy in the Department of Ophthalmology, Tokyo Medical University Hospital were studied. We measured VEGF concentrations in vitreous humor collected at the time of vitrectomy using ELISA. IVB injections were performed after vitrectomy in patients with vitreous VEGF levels exceeding 1,000 pg/mL. New bleeding occurring within 1 month of vitrectomy was defined as early vitreous hemorrhage (VH). Main outcome measure: The incidence of complications after vitrectomy including postoperative early VH. Results: IVB injections were administered to 11 eyes (26%) with vitreous VEGF concentrations exceeding 1,000 pg/mL. None of the 11 eyes that received an IVB injection developed early VH. Among 31 eyes (74%) with vitreous VEGF concentrations lower than 1,000 pg/mL, two eyes (6%) developed early VH after vitrectomy. Conclusions: Prophylactic IVB injections administered to patients with elevated preoperative intraocular VEGF concentrations were effective in preventing post-vitrectomy early VH.Keywords: diabetic retinopathy, VEGF, vitreous hemorrhage, intravitreal bevacizumab injection